2013
DOI: 10.1134/s0031918x1309007x
|View full text |Cite
|
Sign up to set email alerts
|

Elastic fields of (774)γ[4 4 $\overline {14} $ ]γ crystons and the formation of a lath structure of bainitic ferrite

Abstract: An analysis has been performed for elastic fields of crystons that simulate the carriers of shear deformation on planes close to the habit plane of the additional to {558} γ component of the bimodal distri bution of ferrite habits in a bainite macroplate. The conclusion has been drawn that the additional component arises according to the same mechanism as the main component, but in the region of austenite with a twin orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As compared with separate loops, crystons have a modified angular distribution of the elastic field (primarily, due to a change in the Burgers vectors), as well as a cumulative effect ensuring strengthening of the field. This variant of the influence of crystons on the formation of CIM illustrates in pretty much detail the results described in [31].…”
Section: Main Areas Of the Cryston Concept Application To The Formatimentioning
confidence: 66%
“…As compared with separate loops, crystons have a modified angular distribution of the elastic field (primarily, due to a change in the Burgers vectors), as well as a cumulative effect ensuring strengthening of the field. This variant of the influence of crystons on the formation of CIM illustrates in pretty much detail the results described in [31].…”
Section: Main Areas Of the Cryston Concept Application To The Formatimentioning
confidence: 66%
“…In particular, this approach demonstrates good reproduction of the conditions needed to obtain the initial DNCs. In [7], we concluded that the data of the experiment and analysis speak in favor of the hypoth esis on the formation of ferrite laths with habit planes (774) γ in austenite regions with a twin orientation. In connection with this, the problem arises of determin ing how twinned austenite regions are formed.…”
Section: Introductionmentioning
confidence: 90%
“…As has been shown in [5,7], the decisive role in the description of the habits of the {hhᐉ} γ type belongs to the segments of the DNCs located along the close packed directions Λ 1 The formation of each ferrite lath is accompanied by a macroshear with the principal component lying in the habit plane.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations